Development and calibration of an accurate 6-degree-of-freedom measurement system with total station. (28th October 2016) - Gao, Yang; Lin, Jiarui; Yang, Linghui; Zhu, Jigui
Abstract: To meet the demand of high-accuracy, long-range and portable use in large-scale metrology for pose measurement, this paper develops a 6-degree-of-freedom (6-DOF) measurement system based on total station by utilizing its advantages of long range and relative high accuracy. The cooperative target sensor, which is mainly composed of a pinhole prism, an industrial lens, a camera and a biaxial inclinometer, is designed to be portable in use. Subsequently, a precise mathematical model is proposed from the input variables observed by total station, imaging system and inclinometer to the output six pose variables. The model must be calibrated in two levels: the intrinsic parameters of imaging system, and the rotation matrix between coordinate systems of the camera and the inclinometer. Then corresponding approaches are presented. For the first level, we introduce a precise two-axis rotary table as a calibration reference. And for the second level, we propose a calibration method by varying the pose of a rigid body with the target sensor and a reference prism on it. Finally, through simulations and various experiments, the feasibilities of the measurement model and calibration methods are validated, and the measurement accuracy of the system is evaluated.